Drought tolerance gene pool in developing adaptive varieties of durum wheat identified in study nurseries under the Kazakhstan-Siberian program - M. G. Evdokimov; V. S. Yusov; A. I. Morgounov; Yu. I. Zelensky (Вавиловский журнал генетики и селекции)
Drought during the wheat vegetative period happens often in West Siberia and Kazakhstan condition. For this reason, varieties with adaptation to climatic zones, drought tolerance and high stability have high importance. The breeding efficiency and rates depend on the amount of information on genotypes in every study cycle. The aim of this study was to screen breeding material in Siberian and Kazakhstan research institutes from KASIB nurseries for drought tolerance and to develop a drought tolerant pool. For the evaluation of genotypes, it is necessary to study them in diverse condition. The basic purpose of the present work is to study breading material of durum wheat from KASIB institutions at different ecological sites. In 2000–2015, durum wheat entries in the Kazakhstan-Siberian program were studied. Progress in durum wheat breeding was tested in Russian and Kazakhstan institutes. Entries were screened for drought tolerance, yield and yield stability. They have value for including in hybridization for developing varieties with adaptation to Siberian and Kazakhstan conditions. The following varieties and lines are recommended for breading for drought tolerance: 383-МС, 452-МС, Каrgala 303, Каrgala 447, Каrgalа 24, Каrgala 1515/06, Каrgala 1516/06, Каrgala 69, Каrgala 1538, Каrgalа 1540, Каrgalа 1539, Kargalа 1671, Каrgalа 1411 (Акtubinsk Agricultural Experimental Station), Hordeiforme 91-25-5, Hordeiforme 91-22-2, Jemthujina Sibiri, Hordeiforme 94-94-13, Hordeiforme 98-42-1, Hordeiforme 01-121-3, Hordeiforme 02-156-1 (Siberian Research Agricultural Institute), Аltin schigis, Аltin dala, Line Г1549 (Каrabalyk Experimental Station), Hordeiforme 373, Hordeiforme 627 (Altai Research Agricultural Institute), 17394, 18053, Nauriz-6 (Кazakh Research-Production Center of Agriculture and Plant Growing), Коllektivnaya 2, ТС-15 (Kurgan Research Agricultural Institute), Line 653d-4 (Sаmara Research Agricultural Institute).